Cefazolin as a Prophylactic Antibiotic in Laparoscopic Cholecystectomy: A Systematic Review - Tjokorda Gde Agung Senapathi (Journal of Global Pharma Technology, 2020)
Background: Cefazolin is a first-generation cephalosporin prophylactic antibiotic which recommended for open cholecystectomy. Laparoscopic cholecystectomy is a clean contaminated surgery that does not require prophylactic antibiotics. Some surgeons still have the habit of giving prophylactic antibiotics for laparoscopic cholecystectomy. This systematic review aimed to examine evidence from randomized controlled trials comparing the incidence of surgical wound infection with cefazoline use. Methods: We collected randomized controlled trials (RCTs) throughout the years 2010-2020 from the Cochrane Library and PubMed in English language, which examined the incidence of surgical wound infection between the cefazolin prophylactic antibiotic groups versus placebo on laparoscopic cholecystectomy. Results: Six RCTs were included in the final analysis for a qualitative assessment using the Jadad scale, with four articles in the high category and the other two in the good category. The incidence of surgical wound infection in the cefazolin group was 1.09-4.8% (mean 2.63%) and did not differ significantly from the placebo group. Old age (> 60 years), obesity, timing of antibiotics, as well as tissue trauma and billiard spill during laparoscopic cholecystectomy were not significant factors. Conclusion: The prophylactic antibiotic cefazolin was not significant in reducing the incidence of surgical wound infection in lapaoscopic cholecystectomy. It is necessary to review the guidelines for prophylactic antibiotics in each health service place. Keywords: Cefazolin, Prophylactic antibiotics, Laparoscopic cholecystectomy, Surgical wound infection.